Development of Antibacterial Mtcu/Pla Nanocomposites by Casting Method for Potential Use in Food Packaging - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (Sociedad Chilena de Quimica, 2015)
Polylactic acid (PLA) nanocomposites with two antimicrobial agents based on copper modified montmorillonite (MtCu2+ and MtCu0) were developed in order to obtain a lower environmental impact material with antimicrobial activity for potential use in food packaging. Clay modification was permorfed by cation exchange between MtNa+ and a copper salt obtaining MtCu2+ and its followed reduction with NaBH4 obtaining MtCu0. Then PLA nanocomposite films (MtCu2+/PLA and MtCu0/PLA), using different concentration of MtCu2+ and MtCu0 (1, 3 and 5 wt.%) were obtained by casting technique. X-ray diffraction (XRD) and Transmission electronic microscopy (TEM) analysis evidenced a certain degree of intercalation of the modified clays in the nanocomposites. Thermal, mechanical and optical properties showed variations by incorporating MtCu2+ and MtCu0 in the polymer matrix. On the other hand, it was possible to evidence antimicrobial activity of the nanocomposites (ASTM Standard E2149) against to Escherichia coli ATCC 25922 and Listeria innocua ATCC 33090 obtaining a 99% maximum of reduction to both bacteria.